A Reforma do Ensino Médio (LEI Nº 13.415/17) em Goiás: o caso do Centro de Ensino de Período Integral – CEPI Professor Pedro Gomes - Jacob, Hemanuelle Di Lara Siqueira (2025)
This thesis, developed within the Graduate Program of the Faculty of Education (PPGE) at the Federal University of Goiás (UFG), focuses on the High School Reform in Brazil, established by Law No. 13,415/2017, with an emphasis on its implementation in the state of Goiás. The research analyzes the impacts of this reform on the Full-Time Teaching Center (CEPI) Professor Pedro Gomes, located in Goiânia-GO, seeking to understand its effects on pedagogical work, curricular organization, and the perceptions of teachers, students, and administrators. The investigation adopted a qualitative approach based on historical-critical analysis, characterizing itself as a case study, in accordance with the methodologies of Triviños (2005) and André (2008). Data collection was conducted through unsystematic observations, semi-structured interviews with teachers and administrators, focus groups with students, and document analysis. Institutional and regulatory documents regarding the implementation of the reform at the national and state levels were analyzed, including legislation, opinions, and pedagogical guidance. Additionally, the state of the art of academic production on the New High School was taken into account, using sources from the Brazilian Digital Library of Theses and Dissertations (BDTD), based on the descriptors "Implementation of the National New High School," "Implementation of the New High School in Goiás," and "Implications arising from the implementation of the New High School." The theoretical framework was based on critical studies of education and neoliberal policies, referencing Losurdo (2006), Moraes (2001), and Neto and Braz (2006). Furthermore, the works of Saviani (2003), Giroux (1997), and Apple (2006) were mobilized to analyze the contradictions and resistances in education. The results indicate significant challenges in the implementation of the New High School at the investigated school unit. The curricular flexibility resulted in an increased workload for teachers, accompanied by a reduction in the hours allocated to all traditional subjects, with Sociology, Philosophy, Arts, and Physical Education being the most affected, compromising the quality of education. In light of this scenario, the school sought resistance strategies, promoting internal arrangements and interdisciplinary projects to mitigate curricular dilution. Student perceptions revealed ambiguous positions regarding the reform. While some appreciated the technical and professional training, there were concerns about the superficiality of the content and the precariousness of preparation for higher education. However, there was consensus among students that the New High School did not contribute to an improvement in the quality of education, nor did it allow them to make effective choices regarding their educational pathways. In terms of school management, there was an observable effort to adapt to the new guidelines, although facing structural limitations due to lack of resources and institutional support. Additionally, resistance from the teaching staff was identified concerning the new curricular architecture, as teachers reported workload overload, pedagogical difficulties, and a perceived decline in the quality of education.In this context, the research highlights the need for public policies that value teaching work and promote greater educational equity. A critical review of the implementation of the reform is essential to ensure quality, comprehensive, and emancipatory education that addresses the demands and socioeconomic diversities of Brazilian students.